2018
DOI: 10.1016/j.bja.2017.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sleep in patients with chronic pain

Abstract: were included. Analysis showed a small reduction [À6.47 (À8.78, À4.17), P<0.00001] in postoperative pain intensity reported by patients treated with parecoxib compared to controls. Small reductions in the use of rescue analgesia in both the immediate postoperative period and 24 h following surgery were also seen in patients treated with parecoxib. No studies reported any serious adverse events related to parecoxib administration. The impact of parecoxib, when used in this manner, appears to be limited to a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…There was insufficient evidence of the benefit of melatonin in BMS. The relationship between pain and sleep is inextricable, in which poor sleep quality is a risk factor for chronic pain development, and pain disrupts the sleep pattern ( 98 ). Melatonin is a neurohormone that regulates the circadian biological rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…There was insufficient evidence of the benefit of melatonin in BMS. The relationship between pain and sleep is inextricable, in which poor sleep quality is a risk factor for chronic pain development, and pain disrupts the sleep pattern ( 98 ). Melatonin is a neurohormone that regulates the circadian biological rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic non-cancer pain (CNCP) is defined as pain that is not resolved in an expected time-frame, does not respond to acceptable analgesic treatment, and lasts more than three months ( Tunks et al, 2008 ). CNCP has a negative impact on sleep ( Vaughan et al, 2018 ) and on patients’ physical, psychological and social wellbeing, which when combined, are often defined as health-related quality of life (QoL) ( Jensen et al, 2007 ). QoL is one of the important outcome domains being measured in the evaluation of pain treatment effectiveness and has been suggested to be indicative of treatment success ( Börsbo et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The primary outcome measure is improved sleep disturbance, measured using the Verran Snyder-Halpern (VSH) scale,31 which assesses sleep over the previous 24 hours. Our previous study showed that patients with mild pain (average pain score of 4 or less) compared with severe pain (scoring 7 or more) had median VSH sleep disturbance scores of 147 and 490, respectively 6. Assuming a conservative treatment effect difference of 120 (effect size=0.60), we need a minimum of 46 patients to achieve 80% power.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Epidemiological reports suggest that over 50% of individuals with chronic pain experience disturbed sleep 2–5. The risk of poor sleep quality increases as patient-reported pain intensity increases 6. Both chronic pain and sleep disturbance independently diminish quality of life and have a detrimental effect on mental health and well-being 5.…”
Section: Introductionmentioning
confidence: 99%